Operation Final Notice - Landis, Matthew (Dial Books for Young Readers, 2024)
"As Christmas and the new year inch closer, so do Ronny and Jo's anxieties. Ronny needs $878 to keep his family's only car from getting taken by the bank. Ever since a workplace injury disabled his dad and forced the family to move from their home into the apartment complex across the street, Ronny's had a crash course in repossession. His best friend, Josefina Ramos, is also counting down until the start of January, when her life could change forever - that's when she has her big cello audition at the prestigious music academy Maple Hill. Except she can't play a solo performance without something disastrous happening and no one seems to hear her when she talks about how nervous she is. Told from Ronny's and Jo's alternating points of view, this heart-warming story is about what happens to best-laid plans and learning how to depend on each other and their community when things get tough"--Cover.